2020
DOI: 10.1039/d0cp01243b
|View full text |Cite
|
Sign up to set email alerts
|

Highly branched triple-chain surfactant-mediated electrochemical exfoliation of graphite to obtain graphene oxide: colloidal behaviour and application in water treatment

Abstract: The generation of surfactant-assisted exfoliated graphene oxide (sEGO) by electrochemical exfoliation is influenced by the presence of surfactants, and in particular the hydrophobic tail molecular-architecture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 78 publications
0
3
0
Order By: Relevance
“…The obtained rEGO films with different surfactants after the filtration and reduction treatment were named TC14-rEGO and PDDA-rEGO, respectively. TC14 has been proved as an ideal surfactant for stabilizing graphene oxide, thanks to its unique triple-chain branched structure that could effectively prevent the aggregation of graphene flakes during the reduction process, 40 while PDDA has been widely used as a linker for the self-assembly of 2D nanomaterials. 41 XRD spectra of these films ( Figure 6 f) suggest that the TC14-rEGO diffraction peak has no apparent difference compared to the rEGO peak without TC14.…”
Section: Resultsmentioning
confidence: 99%
“…The obtained rEGO films with different surfactants after the filtration and reduction treatment were named TC14-rEGO and PDDA-rEGO, respectively. TC14 has been proved as an ideal surfactant for stabilizing graphene oxide, thanks to its unique triple-chain branched structure that could effectively prevent the aggregation of graphene flakes during the reduction process, 40 while PDDA has been widely used as a linker for the self-assembly of 2D nanomaterials. 41 XRD spectra of these films ( Figure 6 f) suggest that the TC14-rEGO diffraction peak has no apparent difference compared to the rEGO peak without TC14.…”
Section: Resultsmentioning
confidence: 99%
“…However, studies have revealed that the hydrophobic base with a branched structure show better wetting and penetrating properties than those of linear ones, even when their types and molecular sizes are comparable. [11][12][13][14][15] Sha and coworkers successfully synthesized a novel branched uorinated anionic surfactant 4-(3,3,4,4,5,5,5-heptauoro-2,2-bis-triuoromethyl-pentyl)-benzene lithium phosphonate via a four-step route by using peruoro-2-methyl-2-pentene as a starting material. 16 This branched uorinated anionic surfactant exhibits excellent surface activity, which reduces the surface tension of water to be 19.2 mN m À1 .…”
Section: Introductionmentioning
confidence: 99%
“…Different from ultrasonic exfoliation and thermal exfoliation, electrochemical exfoliation is an energy-efficient and environmentally friendly method to get carbon nanosheets. 1,2 The obtained carbon nanosheets(CNSs) exhibited large surface area and good surface activity, which can be used in various fields such as electroanalysis, 3,4 adsorption separation 5,6 and energy store. 7,8 In order to get CNSs with better performance, various electrochemical exfoliation methods have been explored.…”
mentioning
confidence: 99%